2011
DOI: 10.1109/lmwc.2010.2102011
|View full text |Cite
|
Sign up to set email alerts
|

A 0.6 V 10 GHz CMOS VCO Using a Negative-Gm Back-Gate Tuned Technique

Abstract: Without an extra on-chip accumulation-mode MOS varactor, a voltage-controlled oscillator (VCO) using a negative-transconductance back-gate tuned technique is demonstrated in a standard 0.18 mu m CMOS process to achieve low-voltage, wide-range and high-frequency designs. Employing the varied p-n junction capacitance and the varied transconductance in the intrinsic-tuned regime, the VCO provides the tuning range of 9.95 to 11.05 GHz at a 0.6 V supply and dissipates below 4.35 mW. At 11 GHz carrier frequency, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The comparison of these VCO with other previously published 10GHz LC-VCO is summarised in Table 3. Table 3 has shown that the proposed 10GHz LC-VCO has achieved an improvement of FOM and phase noise at 1MHz offset frequency by -4.3dBc/Hz and -5.87dBc/Hz compared with similar VCO in [30]. It also has the lowest phase noise compared with VCOs from other literature.…”
Section: Results and Comparisonmentioning
confidence: 82%
“…The comparison of these VCO with other previously published 10GHz LC-VCO is summarised in Table 3. Table 3 has shown that the proposed 10GHz LC-VCO has achieved an improvement of FOM and phase noise at 1MHz offset frequency by -4.3dBc/Hz and -5.87dBc/Hz compared with similar VCO in [30]. It also has the lowest phase noise compared with VCOs from other literature.…”
Section: Results and Comparisonmentioning
confidence: 82%
“…An X ‐band CMOS VCO with built‐in envelope detection is designed and measured. Compared with other X ‐ and Ku ‐band CMOS VCOs listed in Table , our VCO exhibits wide tuning range of 31.7% and good FoM T of −192.5 dBc/Hz at 1‐MHz offset. The VCO is designed with on‐chip envelope detectors at the output.…”
Section: Resultsmentioning
confidence: 96%
“…Complementary LC tank VCO structures presented in [2, 3] have a limited voltage supply and cannot operate in the near‐threshold region. To increase tuning range, a VCO designed in [4] employs a negative‐transconductance back‐gate tuned technique, instead of the conventional MOS varactors. Using an active inductor [5] for the LC tank reduces the quality ( Q ) factor of the tank circuit, resulting in phase noise degradation.…”
Section: Introductionmentioning
confidence: 99%